Penguatan Karakter Peserta Didik Melalui Pembelajaran IPS Terpadu - Sri Wahyuni; Bongguk Haloho; Ulung Napitu; Corry Corry (Departement of Mathematics Education, 2023)
Character is inherent in every individual which is reflected in behavior patterns in everyday life. A person's character is influenced by environmental factors (nurture) and innate factors (nature). This character education aims to develop a person's ability to make good and bad decisions, maintain what is good, and realize that goodness in everyday life wholeheartedly. Where at this time the condition of the Indonesian nation is experiencing a decline in character. We realize that if this demoralization is not corrected immediately, this nation that we love will be on the brink of collapse. Therefore character education is a habit, so the formation of one's character requires communities of character. The role of schools as communities of character in character education is very important. Schools develop character education processes through learning processes, habituation, extracurricular activities, and working with families and communities in their development.